Born again bodies : flesh and spirit in American Christianity - Griffith, R. Marie (Ruth Marie), 1967- (California studies in food and culture, 2004)
'Born Again Bodies' explores a modern manifestation of religious asceticism. Using literature with titles such as 'What Would Jesus Eat?' the promoters of Christian diet programmes are enrolling hundreds of thousands of Americans prepared to believe that fat people won't make it to heaven.